Ezra, Nehemiah, Esther - Breneman, Mervin (Nashville, TN Broadman and Holman, 1993)
Includes bibliographical references and indexes.
Keywords: Bible. O.T. Ezra -- commentaries; Bible. O.T. Nehemiah -- commentaries; Bible. O.T. Esther -- commentaries